Desafios do ensino jurídico: a influência do estágio no curso de graduação em direito - Amorim, Paulo Henrique Castilho (2011)
This research deals with the theme - Challenges of Legal Education: The , , , , , , , , , , , , , influence of the stage in the undergraduate course in law. The researcher became interested in the topic because of his personal experience, first as student and later as a teacher. When a student, I needed to start an internship in the first year of the course, and most colleagues would only do the stage over the past two years. I realized that because of the practice, I had a better meaning of the theory, which helped me not only in degree, but the proof of OAB and in my professional life as a lawyer. This reality comes the research problem: What is the contribution of legal practice in undergraduate training in law? Object of study: The two lines of existing stage in the teaching of law; The Supervised completed within the IES under the supervision of a teacher and Stage Unsupervised Advocacy office held in private or agreements with the Court. The objective was to evaluate the contribution offered by each form of training, to graduate in law. It has been hypothesized: If the students from the Law have greater contact with during the course content practical, will mean greater ease in learning theory, besides leaving to take the best and Order advocacy. Methodology: An exploratory study using qualitative approach. Methodology: literature review, case study with conducting interviews and questionnaire response. Theoretical Framework: We used the area of education and law between them, Bastos (1998), Bastos (2000); Bitar (2001); MELO FILHO (1984), Rodrigues (1993) among others. The research showed that students who had greater contact with during the course practical contents, performing stage had not supervised mean greater ease in learning theory, besides d do better to take the order and law.